Impact of 2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-D-glucoside on cognitive deficits in animal models of Alzheimer's disease: a systematic review. Issue 1 (December 2016) - Sheng, Chenxia; Peng, Weijun; Chen, Zeqi; Cao, Yucheng; Gong, Wei; Xia, Zi-an; Wang, Yang; Su, Nanxiang; Wang, Zhe
Abstract Background The efficacy of 2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-D-glucoside (TSG) treatment on cognitive decline in individuals with Alzheimer's disease (AD) has not been investigated. Therefore, we systematically reviewed the effect of TSG on cognitive deficits in a rodent model of AD. Methods We identified eligible studies published from January 1980 to April 2015 by searching seven electronic databases. We assessed the study quality, evaluated the efficacy of TSG treatment, and performed a stratified meta-analysis and meta-regression analysis to assess the influence of study design on TSG efficacy. Results Among a total of 381 publications, 18 fulfilled our inclusion criteria. The overall methodological quality of these studies was poor. The meta-analysis revealed a statistically significant benefit of TSG on acquisition memory (standardized mean difference [SMD] = −1.46 (95 % CI: −1.81 to −1.10, P  < 0.0001) and retention memory (SMD =1.93 (95 % CI: 1.40 to 2.46, P  < 0.0001) in experimental models of AD. The stratified analysis revealed a significantly higher effect size for both acquisition and retention memory in studies that used mixed sex models and a significantly higher effect size for acquisition memory in studies that used transgenic models. Conclusions Our meta-analysis highlights a significantly better treatment effect in rodent AD models that received TSG that in those that did not. These findings indicate a potential therapeutic role of TSG in AD therapy. However, additional well-designed and detailed experimental studies are needed to evaluate the safety of TSG.